Foodborne Outbreak and Nonmotile Salmonella enterica Variant, France - Le Hello, Simon (Centers for Disease Control and Prevention, 2012)
We report a food-related outbreak of salmonellosis in humans caused by a nonmotile variant of Salmonella enterica serotype Typhimurium in France in 2009. This nonmotile variant had been circulating in laying hens but was not considered as Typhimurium and consequently escaped European poultry flock regulations.